2010
DOI: 10.3763/ijas.2009.0465
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture on the edge: strategies to abate urban encroachment onto agricultural lands by promoting viable human-scale agriculture as an integral element of urbanization

Abstract: In the Greater Vancouver region (Canada) tensions exist where urbanization encroaches onto agricultural land. A recently issued white paper proffered ideas to stimulate discussion on land-use plans and public policies to encourage and enhance agriculture while accommodating a doubling of the region's population. It evoked a visceral response from local and regional politicians, planners and agrologists who saw it as an heretical attempt to undermine land conservation. Proponents saw innovative strategies to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 4 publications
0
23
0
2
Order By: Relevance
“…The majority of LS farms in this study were land-less, and almost all feeds were scavenged and/or purchased from other regions. Condon et al (2010) and Nigussie et al (2015) also reported shortage of land as the main constraint for urban farmers. Land is very expensive in urban areas, and priority is given to residential areas and commercial centers demanded by the rapidly growing urban population at the rate of 3.8, 4.5 and 3.0% per year in Addis Ababa, Adama and Jimma, respectively (Haile Mariam and Adugna 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of LS farms in this study were land-less, and almost all feeds were scavenged and/or purchased from other regions. Condon et al (2010) and Nigussie et al (2015) also reported shortage of land as the main constraint for urban farmers. Land is very expensive in urban areas, and priority is given to residential areas and commercial centers demanded by the rapidly growing urban population at the rate of 3.8, 4.5 and 3.0% per year in Addis Ababa, Adama and Jimma, respectively (Haile Mariam and Adugna 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Within Metro Vancouver, the City of Surrey exhibited the highest growth rate during the most recent census period, and is now home to 19 percent of the province's population (468,251). This has placed enormous development pressure on agricultural lands and resulted in a situation in which the real estate value of ALR land is far in excess of that justified by any form of production agriculture (Condon et al, 2010). In economic terms, the opportunity cost of ALR land being used for agricultural purposes is too high.…”
Section: With City Of Surrey Highlightedmentioning
confidence: 99%
“…This has encouraged profligate establishment of rural residences and various non-farm ALR land use, especially in peri-urban regions such as metroVancouver. It has also been observed that the ALR has functioned as a de facto urban growth boundary in B.C., and in metropolitan areas (especially) the ALR has not curtailed speculative land holding (Condon, Mullinix, Fallick, & Harcourt, 2010). In the City of Surrey, approximately 8,787 hectares (21,713 acres) were designated as part of the ALR.…”
Section: With City Of Surrey Highlightedmentioning
confidence: 99%
“…L'émer-gence récente des AMAP (Association pour le Maintien de l'Agriculture Paysanne), l'engouement pour les circuits courts de commercialisation, et plus généralement les attentes sociétales vis-à-vis d'une alimentation plus saine, (Nickerson, 1997) ont fait redécouvrir une activité qui semblait ne plus avoir sa place dans l'espace urbain. Désormais l'espace agricole intra-urbain fait l'objet d'une réflexion globale dans les projets sur la ville, comme l'illustre l'apparition d'opérations d'agri-urbanisme (Condom et al, 2010).…”
Section: Introductionunclassified